2006
DOI: 10.1124/jpet.105.099051
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Heme Oxygenase-1 Is Involved in Carbon Monoxide-Mediated Central Cardiovascular Regulation

Abstract: Carbon monoxide (CO) has been identified as an endogenous biological messenger in the brain. Heme oxygenase (HO) catalyzes the metabolism of heme to CO and biliverdin. Previously, we have shown the involvement of CO in central cardiovascular regulation, baroreflex modulation, and glutaminergic neurotransmission in the nucleus tractus solitarii (NTS) of rats. In this study, we examined which HO isoform could be induced after hemin injection in the NTS. We also investigated their in situ distributions in the NTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
2
12
1
Order By: Relevance
“…Direct injection of hematin into the NTS consistently lowers blood pressure and heart rate. 40,41 The depressor effects of hematin injection into the NTS are similar to those observed with injection of the excitatory amino acid glutamate. Glutamate is the principle neurotransmitter of baroreceptor afferent fibers, which terminate in the NTS.…”
Section: Co and The Brain: Co As A Modulator Of Baroreceptor Functionsupporting
confidence: 57%
“…Direct injection of hematin into the NTS consistently lowers blood pressure and heart rate. 40,41 The depressor effects of hematin injection into the NTS are similar to those observed with injection of the excitatory amino acid glutamate. Glutamate is the principle neurotransmitter of baroreceptor afferent fibers, which terminate in the NTS.…”
Section: Co and The Brain: Co As A Modulator Of Baroreceptor Functionsupporting
confidence: 57%
“…Few studies have directly shown that central HO-CO signaling in the nucleus tractus solitarius (NTS) exerts a tonic restraining influence on sympathetic activity and blood pressure (Johnson et al, 1997;Lo et al, 2006). Although the NTS modulates sympathetic activity and blood pressure, at least partly, via projections to the RVLM (Guyenet et al, 1990), there are no reports on the role of the RVLM HO in blood pressure regulation.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, ZnPPIX (1 nmol; dissolved in 35% dimethyl sulfoxide in aCSF), in a dose used to inhibit HO-1 in the NTS in conscious normotensive rats (Lo et al, 2006), was microinjected into the RVLM of conscious SHRs or WKY rats 30 min before hemin. It is noteworthy that compared with aCSF microinjection of a similar concentration of dimethyl sulfoxide in aCSF into rat brainstem had no impact on baseline blood pressure or its response to subsequent pharmacologic interventions (Tsukamoto et al, 2002).…”
Section: Protocols and Experimental Groupsmentioning
confidence: 99%
See 2 more Smart Citations